Relationship between morphological characters and yield components in plantains - Arantes, Alessandro de Magalhães; Donato, Sérgio Luiz Rodrigues; Silva, Sebastião de Oliveira e (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to assess the magnitude and significance of associations between morphological traits and yield of plantains. Five genotypes were evaluated: Terra, Terra-maranhão, Terrinha, and D'Angola (AAB), besides the hybrid Fhia-21 (AAAB). The associations of bunch weight (BW) with plant characters were not significant, for most of the genotypes. When all genotypes were analyzed simultaneously, most of the evaluated traits showed significant correlations between themselves. In this case, BW was significantly correlated to all traits except fruit-skin thickness.